Analisis Dan Perancangan Aplikasi Sistem Informasi Simpan Pinjam Berbasis Android Versi 2.3 Pada Koperasi Credit Union Jakarta - Budi Wasito (Jurnal Informatika dan Bisnis, 2014)
The transaction processes of saving and credit are very important for the development and prosperity of a cooperative. Although with the rise of information technology development these days, Credit Union Jakarta cooperative is still haven’t had any information system application that supports the transaction processes and information of saving and credit of the members. By utilizing the development of smartphones, writer designs an information system application for the Credit Union Jakarta cooperative so that it supports the delivering process of saving and credit information which are needed by the cooperative members. The information system application of Credit Union Jakarta cooperative focuses on the easiness of accessing saving and credit information by the cooperative members by their own cell phones. Added with the inbox feature, this androidbased application gives the members to interact and to share information among each member easily. The result of this research is an android-based information system application that gives easiness especially to the cooperative members on doing the transaction and checking process of saving and credit. With the help of this application, members not only unnecessary to come to the cooperative but also the loan proposal will be faster. This research comes to a conclusion that the android-based information system application on Credit Union Jakarta cooperative not only gives information such as saving and credit balance, but also gives easiness in the deposit and payment process either for the members or the cooperative itself.